2007
DOI: 10.1590/s0100-879x2006005000082
|View full text |Cite
|
Sign up to set email alerts
|

Description of Lyme disease-like syndrome in Brazil: is it a new tick borne disease or Lyme disease variation?

Abstract: An emerging clinical entity that reproduces clinical manifestations similar to those observed in Lyme disease (LD) has been recently under discussion in Brazil. Due to etiological and laboratory particularities it is named LD-like syndrome or LD imitator syndrome. The condition is considered to be a zoonosis transmitted by ticks of the genus Amblyomma, possibly caused by interaction of multiple fastidious microorganisms originating a protean clinical picture, including neurological, osteoarticular and erythema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 7 publications
(7 reference statements)
0
13
0
Order By: Relevance
“…Mantovani et al (2007) were unable to confirm whether this syndrome is caused by new Borrelia species or it is related to genetically modified Borrelia burgdorferi sensu lato microorganisms or other infectious agent.…”
Section: Introductionmentioning
confidence: 92%
“…Mantovani et al (2007) were unable to confirm whether this syndrome is caused by new Borrelia species or it is related to genetically modified Borrelia burgdorferi sensu lato microorganisms or other infectious agent.…”
Section: Introductionmentioning
confidence: 92%
“…However, the spirochete of Borrelia spp. has not been isolated yet, even after the attempts in samples of human material, ticks and wild animals (Costa et al, 2002;Mantovani et al, 2007) The tick Amblyomma americanum has been identified as the host of the Borrelia lonestari in southern United State (Barbour and Hayes, 1996) and Varela et al (2007) isolated B. lonestari from A. americanum and cultivated it in embryonic cells of Ixodes scapularis (ISE6). Munderloh and Kurtti (1995) observed that the adherence of B. burgdorferi to the cells of R. appendiculatus correlated with infectivity and viability.…”
Section: Discussionmentioning
confidence: 99%
“…The present study found adherence and development of spirochetes to the cells of R. microplus and A. cajennense. The development of this type of study is important because these ticks are involved in the transmission of spirochetes of the genus Borrelia in Brazil (Fonseca et al, 2005;Mantovani et al, 2007;Yoshinari et al, 2010). Rezende et al (2008) demonstrated the occurrence of Borrelia spp.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations